A Comparison of Two Gears for Quantifying Abundance of Lotic-Dwelling Crayfish. Issue 1 (1st January 2014) - Williams, Kristi; Brewer, Shannon K.; Ellersieck, Mark R.
Abstract: Crayfish (saddlebacked crayfish, Orconectes medius ) catch was compared using a kick seine applied two different ways with a 1-${{\rm{m}}^2}$ quadrat sampler (with known efficiency and bias in riffles) from three small streams in the Missouri Ozarks. Triplicate samples (one of each technique) were taken from two creeks and one headwater stream ($n = 69$ sites) over a two-year period. General linear mixed models showed the number of crayfish collected using the quadrat sampler was greater than the number collected using either of the two seine techniques. However, there was no significant interaction with gear suggesting year, stream size, and channel unit type did not relate to different catches of crayfish by gear type. Variation in catch among gears was similar, as was the proportion of young-of-year individuals across samples taken with different gears or techniques. Negative binomial linear regression provided the appropriate relation between the gears which allows correction factors to be applied, if necessary, to relate catches by the kick seine to those of the quadrat sampler. The kick seine appears to be a reasonable substitute to the quadrat sampler in these shallow streams, with the advantage of ease of use and shorter time required per sample.